A DGS monopole antenna loaded with U‐shape stub for UWB MIMO applications. Issue 9 (23rd May 2019) - Hasan, Md Nazmul; Chu, Son; Bashir, Shahid
Abstract: A defected ground structure‐based rectangular monopole antenna along with 2 × 2 and 4 × 4 multiple‐input multiple‐output (MIMO) antennas are presented. The proposed monopole antenna consists of a defected ground structure with two slits and a notch placed at optimum positions to increase the impedance bandwidth. Besides, the radiator is loaded with a U‐shape stub to improve the impedance matching of the antenna. The measured impedance bandwidth of the proposed monopole antenna is from 3.18 to 11.5 GHz. Time domain experiment is carried on to investigate the dispersion characteristics of the proposed antenna. Measurement results reveal that the proposed antenna can retain the transmitted pulse shape, ensuring dispersion‐free communication. Far‐field measurements confirm omnidirectional radiation patterns over the operating bandwidth. Moreover, MIMO performance of the proposed 2 × 2 and 4 × 4 antenna arrays are evaluated based on isolation, envelop correlation coefficient, diversity gain, and channel capacity loss. The proposed single monopole and MIMO versions of this antenna can be used in portable UWB communication devices.